Chromosomal Looping‐Based Expression Activation System in Yeast. Issue 3 (19th February 2021) - Qiu, Leilei; Wang, Xiaoying; Zhuang, Gui; Ouyang, Xinhao; Huang, Xi
Abstract: There is growing evidence that 3D genome organization is a universal and significant mechanism of gene expression regulation. Tools to manipulate long‐range DNA interactions can advance the accurate control of chromosomal architecture. However, simple eukaryotic systems available to engineer chromosomal looping and gene expression are very limited. This study has developed a tool designated as chromosomal looping‐based expression activation system in yeast (CLEASY). Based on a modified yeast chromosome, it consists of conditionally interacting proteins, distal transcriptional regulatory elements, and a reporter gene. Exogenous chemical or light exposure induces the protein interaction, and results in the proximity of distal regulatory elements bound by these interacting proteins, and ultimately activates the reporter gene. In addition to this controllable induction, this system is compatible with the bivalent Cas9 complexes and their guide RNAs, to ensure target specificity and variability. Therefore, CLEASY can be utilized as a simplified eukaryotic model to engineer DNA looping machinery, and potentially serves as a fast platform to investigate looping mechanism and effective molecules. Abstract : CLEASY toolkit is a simplified eukaryotic model to edit 3D genome architecture. Induced by chemical or light stimulus, DNA looping is engineered, so that gene expression and cell viability can be altered. This toolkit is compatible with CRISPR/Cas9 gene editing system, probing its potential as a fast platform to investigate DNA looping machinery and effective molecules.